Marketing Of Bank Products Through Entrepreneurship Training And Credit Financing For Entrepreneurs Students - Sutikno Sutikno (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to determine the relationship between the variables of entrepreneurship training, and bank financing on the marketing of bank products for entrepreneurial students in the Banten area campus. this study was conducted by involving 300 respondents to entrepreneurial students who were running entrepreneurship between March-August 2020. To find out the relationship between variables by testing research instruments in the form of a scale to measure the variables of entrepreneurship training, and bank financing on the marketing of bank products. analyzed using multiple regression analysis techniques, the results of the study show that entrepreneurship training and bank financing have a positive and significant effect on bank product services, which are dominated by bank financing as a contributor to bank product services that make students interested in entrepreneurship.